ANALISIS PERBANDINGAN PENGGUNAAN BAHAN BAKAR GASOHOL DAN PREMIUM TERHADAP PRESTASI MESIN KENDARAAN DAIHATSU FEROZA - HP, Bambang; Budi Santoso, Edy; Nurtjahyono (JURNAL MEKANIKASISTA, 2024)
The research that I made discusses the transfer of energy sources from premium to bioethanol because the facts in the field state that the use of premium fuel is increasing, this great need is faced with threatening problems, namely as we know that premium is included in non-renewable natural resources so that one day it will run out and there are no other energy sources one day there will be a need for renewable energy sources that are abundant and have more environmentally friendly properties, for that bioethanol is the alternative that I choose. because bioethanol has many benefits compared to using gasoline, including:  More perfect combustion, exhaust gas becomes clean.More spontaneous and light traction  Smooth engine, safe for catalyst engines. Fuel efficient up to 20%  Extends engine life ,Higher octane number,Gasoline-fueled motors when filled with 80% premium + 15% Bioethanol will produce engine performance that is almost the same as being filled with premium fuel and will even produce better engine performance. so that research on the comparison of bioethanol can be developed for research, the results of which are expected to be useful for the Indonesian Army.